Recent trends in gene-targeted therapies and their influence on surgical decision-making in rheumatoid arthritis affecting the hands, feet, and ankles - Du, Xiaolong; Yu, Xingxing; Ou, Xuehai; Cheng, Deliang; Zheng, Changming; Shi, Shaoyan (Frontiers in Medicine, 2026)
Rheumatoid arthritis (RA) is an autoimmune disorder associated with chronic inflammation, progressive deformities of the joints, and limited mobility, especially in the hands, feet, and ankles. Recent discoveries in molecular genetics and immunotherapeutic approaches have enhanced the development of more effective RA medications. Gene-targeted therapy facilitates an accurate regulation of the immune system, ultimately preventing the destruction of joints. The new interventions that prevent the progression of the disease require orthopedic surgeons to reconsider the time and method of conducting surgery. This article discusses the latest developments in the field of gene-targeted therapy and their influence on the decision-making process in surgery. There has been a current change in clinical practice to involve early and preventive interventions for joint pathology to delay the use of surgery until it is unavoidable. These innovative techniques are based on the use of focused medicine and foster interdisciplinary cooperation of experts in orthopedics and rheumatology, which, in turn, increases the mobility of the patient and the overall quality of life.